Imaging the snorkel effect during submerged germination in rice: Oxygen supply via the coleoptile triggers seminal root emergence underwater - Shiono, Katsuhiro; Koshide, Akiko; Iwasaki, Kazunari; Oguri, Kazumasa; Fukao, Takeshi; Larsen, Morten; Glud, Ronnie N. (Frontiers in Plant Science, 2022)
Submergence during germination impedes aerobic metabolisms and limits the growth of most higher plants. However, some wetland plants including rice can germinate under submerged conditions. It has long been hypothesized that the first elongating shoot tissue, the coleoptile, acts as a snorkel to acquire atmospheric oxygen (O2) to initiate the first leaf elongation and seminal root emergence. Here, we obtained direct evidence for this hypothesis by visualizing the spatiotemporal O2 dynamics during submerged germination in rice using a planar O2 optode system. In parallel with the O2 imaging, we tracked the anatomical development of shoot and root tissues in real-time using an automated flatbed scanner. Three hours after the coleoptile tip reached the water surface, O2 levels around the embryo transiently increased. At this time, the activity of alcohol dehydrogenase, an enzyme critical for anaerobic metabolism, was significantly reduced, and the coleorhiza covering the seminal roots in the embryo was broken. Approximately 10 hours after the transient burst in O2, seminal roots emerged. A transient O2 burst around the embryo was shown to be essential for seminal root emergence during submerged rice germination. The parallel application of a planar O2 optode system and automated scanning system can be a powerful tool for examining how environmental conditions affect germination in rice and other plants.